HUBUNGAN KECERDASAN EMOSIONAL DENGAN ETOS KERJA PERAWAT MAGANG DI RUMAH SAKIT BAPTIS KEDIRI - Astarani, Kili (Jurnal Penelitian STIKES Kediri, 2011)
ABSTRACT Emotional intelligence is the capacity for recognizing his own feelings and others, ability to motivate ourselves and ability to manage emotions well in ourselves and in relation with other. Feeling and emotion re almost engaged in nurses’ routine in which every treatment given forces them to acquire high emotional intelligence. The phenomenon will appear on apprenticeship nurses, they always be energetic in doing their jobs which also become their lives. Further, the sprit of working was called work ethics. The objective of the research was to find out the correlation between emotional intelligence and work ethics of apprenticeship nurses on Kediri Baptist Hospital. The design of the research was cross sectional research design. The population was the whole apprenticeship nurses on Kediri Baptist Hospital. The sample was 38 using Total Sampling. The independent variable was emotional intelligence while the dependent variable was work ethics. The data were analyzed using Spearman Rho with significant level α ≤ 0.05. The result showed 28 respondents had a medium emotional intelligence level (73.7 %) and 22 respondents had a medium work ethics (57.9 %). The statistical analysis showed p = 0.001 which means there was correlation between emotional intelligence and work ethics of apprenticeship nurses on Kediri Baptist Hospital. The research showed there was significant correlation between emotional intelligence and work ethics of apprenticeship nurses on Kediri Baptist Hospital. Keywords: emotional intelligence, work ethics, apprenticeship nurses